PERAN SISTEM INFORMASI AKUNTANSI DALAM PENGENDALIAN SIKLUS PERSEDIAAN DAN PERGUDANGAN BERDASARKAN KERANGKA COSO - Zahrah, Fatimah; Putri S, Nur Aisyah; Maulana, Adrian; Apriansyah, Resha (JURNAL LENTERA AKUNTANSI, 2025)
Inventory and warehousing control is an important part of maintaining the effectiveness of a company's operations, as this area is prone to recording errors, loss of goods, and data mismatches. To overcome these problems, companies need an adequate internal control system supported by accurate information technology. This study focuses on reviewing how Accounting Information Systems play a role in strengthening inventory and warehousing cycle control when linked to the five components of the COSO (Committee of Sponsoring Organizations of the Treadway Commission) framework. The research was conducted using the literature review method by analyzing ten national journals published in 2021–2025 that discuss internal control, the implementation of COSO, and the use of SIA in inventory management. The results of the study show that most companies have implemented the COSO component, especially in the information and communication aspects, but there are still weaknesses in control and monitoring activities due to the lack of written SOPs, lack of separation of duties, and inconsistent implementation of stock taking. In addition, companies that have used SIA have proven to have more structured and accurate controls through real-time logging, audit trails, and inter-departmental data integration. Thus, the integration of SIA and the COSO framework contributes significantly to improving the effectiveness of inventory and warehousing control and supporting the company's operational efficiency.